Epidemiological profile of Dengue in the Health Region of Estrada de Ferro, Goiás State, Brazil (Research, Society and Development, 2024)
Objective: To characterize the epidemiological profile of dengue in Goiás over 5 years, focusing on the Estrada de Ferro health region. Methodology: This is a descriptive and retrospective epidemiological study of a quantitative nature. Data were obtained through queries to the Department of Health Informatics of the Unified Health System (DATASUS). The variables considered were the year of notification, age group, sex, and the set of cities within the health region. Results: 780 cases and 14 deaths due to dengue were observed from 2019 to 2023. The municipalities with the highest dengue infection rates were Catalão, with 256 cases (32.9%), Caldas Novas with 116 cases (14.9%), and Pires do Rio with 114 cases (14.6%). It was noted that cases are prevalent among women and adults. Conclusion: The analysis of dengue case distribution in the Estrada de Ferro region reflects the complexity of the disease, both in terms of the total occurrence of cases and the severity variants (sex, age group, and death). Agreement with the literature was found in several observations, although some contradictions and elements generate debates and require further studies.